2016
DOI: 10.1186/s12966-016-0447-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dietary risk factors on the burden of non-communicable diseases in Ethiopia: findings from the Global Burden of Disease study 2013

Abstract: BackgroundThe burden of non-communicable diseases (NCDs) has increased in sub-Saharan countries, including Ethiopia. The contribution of dietary behaviours to the NCD burden in Ethiopia has not been evaluated. This study, therefore, aimed to assess diet-related burden of disease in Ethiopia between 1990 and 2013.MethodWe used the 2013 Global Burden of Disease (GBD) data to estimate deaths, years of life lost (YLLs) and disability-adjusted life years (DALYs) related to eight food types, five nutrients and fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 34 publications
2
54
1
1
Order By: Relevance
“…The magnitude of untreated obvious caries (clinically visible lesions representing demineralisation in the middle third of the dentine, and above indicated by the ICDAS 4 threshold) in the study participants was high; if the early and sub-clinical lesions were included, which would require optimal clinical and radiographic examinations (40), a higher value would result. These ndings suggest an increasing burden of NCDs in general (41). Interestingly, a higher proportion of dental caries experience was observed in rural areas, unlike a previous study in Ethiopia which reported a higher prevalence of caries in urban areas (61.1%) (14).…”
Section: Discussioncontrasting
confidence: 59%
“…The magnitude of untreated obvious caries (clinically visible lesions representing demineralisation in the middle third of the dentine, and above indicated by the ICDAS 4 threshold) in the study participants was high; if the early and sub-clinical lesions were included, which would require optimal clinical and radiographic examinations (40), a higher value would result. These ndings suggest an increasing burden of NCDs in general (41). Interestingly, a higher proportion of dental caries experience was observed in rural areas, unlike a previous study in Ethiopia which reported a higher prevalence of caries in urban areas (61.1%) (14).…”
Section: Discussioncontrasting
confidence: 59%
“…Diets low in fruits and vegetables, nuts and seeds, fish and omega-3 and high in sodium are the five top most important risk factors of NCDs. A study in Ethiopia showed that almost half of CVD deaths were caused by poor diet quality (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that indices of nutritional status, that include low birth weight, stunting and wasting, were associated with increased deaths from CVD. Other workers have shown that suboptimal dietary factors, particularly low intakes of fruits and vegetables, can influence DALYs and deaths from CVD (12,27) . A study in Egypt showed that micronutrient deficiency states co-exist with obesity and that serum Zinc and iron correlated with HDL and negatively with leptin and cholesterol (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of low-quality diets has been associated with the occurrence of noncommunicable diseases and the associated comorbidities such as hypertension and heart diseases. 7 Diets low in fruits and vegetables and high in sodium have been reported to be the most common specific dietary risks for noncommunicable diseases. 7 Biodiversity is linked to dietary diversity where adequate diversity of the diet leads to proper childhood growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…7 Diets low in fruits and vegetables and high in sodium have been reported to be the most common specific dietary risks for noncommunicable diseases. 7 Biodiversity is linked to dietary diversity where adequate diversity of the diet leads to proper childhood growth and development. Reduced dietary diversity has been shown as strong predictor of stunting in children.…”
Section: Introductionmentioning
confidence: 99%